Language Functions in Literary Language Class Interactions Towards the Structure of Observed Learning Outcomes (SOLO Framework) - Briñas, Eleonor; Angeles, Reyna (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study explored the relationship between teachers’ use of language functions and students’ cognitive responses according to the SOLO framework in literature classrooms at Bernardo Lirio Memorial National High School. The research utilized a qualitative approach involving semi-structured interviews with six English teachers, classroom observations, and analysis of lesson plans, assessments, and student outputs. The analysis revealed that heuristic, personal, interactional, informative, divertive, instrumental, imaginative, and regulatory language functions were predominant and systematically guided students from surface-level understanding to higher-order, relational, and extended abstract cognitive responses. The study identified patterns showing that scaffolded questioning, dialogic pedagogy, text-to-self connections, creative reconstructions, playful engagement, differentiated instruction, and metacognitive reflection enhanced analytical, evaluative, and creative thinking. The findings highlighted challenges in aligning instructional strategies with students’ varying cognitive levels and emphasized the importance of intentional use of language functions to promote deeper learning. The study recommends that teachers align classroom discourse with students’ cognitive levels to optimize engagement and learning outcomes. The research supports SDG 4 – Quality Education by promoting inclusive and effective teaching practices, and SDG 10 – Reduced Inequalities by addressing diverse learner needs. Its sustainability impact lies in improving institutional practices, fostering metacognitive development, and enhancing long-term teaching effectiveness.
Keywords: Classroom Interaction; Critical Thinking; Heuristic Function; Literature Instruction; Language Functions; Student Engagement; Thematic Analysis